Continuing professional education experiences and expectations of nurses in Chinese military hospitals: A quantitative and qualitative study. (January 2023) - Ma, Huijuan; Zhang, Suofei; Zhu, Xiaoli; Huang, Jinyu; Cheng, Zhen; Luo, Yu
Abstract: Background: Continuing professional education (CPE) is important for maintaining the competencies of nurses. The evaluation of training needs is necessary for well-organized CPE programs. Objectives: To obtain a deeper understanding of the past experiences and future expectations of CPE among nurses in Chinese military hospitals in order to provide empirical support for planning effective CPE programs. Design: We implemented a two-phase procedure to investigate the experiences and expectations of CPE. Settings: Twenty one hospitals across China. Participants: 382 nurses in quantitative study, and 20 nurses in qualitative study. Methods: Self-designed questionnaire was used to quantitatively measure past experiences, willingness to participate, and future expectations of CPE via a cross-sectional study. Semi-structured interviews were carried out to explore the characteristics of CPE activities among military nurses. Results: A total of 293 (76.7 %) participants had experience with CPE in the past, and 362 (94.8 %) were willing to take CPE in the future. The top five training items they wanted to learn about in the future were combat casualty care, emergency and critical care, military skills, trauma care in an austere environment, and specialist nursing. We identified the following 5 themes in the qualitative data: military missions, military training content, military medicine training content, training methods, and professional development paths. Conclusions: Nursing administrators and educators should consider designing hierarchical, categorized CPE programs to meet the needs of self-development and professional growth among nurses.